2007
DOI: 10.1038/sj.bjp.0707361
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the ecto‐ATPase inhibitor ARL 67156 on human and mouse ectonucleotidases

Abstract: Background and purpose: ARL 67156, 6-N,N-Diethyl-D-b-g-dibromomethylene adenosine triphosphate, originally named FPL 67156, is the only commercially available inhibitor of ecto-ATPases. Since the first report on this molecule, various ectonucleotidases responsible for the hydrolysis of ATP at the cell surface have been cloned and characterized. In this work, we identified the ectonucleotidases inhibited by ARL 67156. Experimental approach: The effect of ARL 67156 on recombinant NTPDase1, 2, 3 & 8 (mouse and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
179
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 58 publications
8
179
0
1
Order By: Relevance
“…It is noteworthy that NPPs prefer alkaline pHs for activity. In our hands, recombinant human NPP1 and NPP3 had only low ATPase activities (compared with those of NTPDases) [17], suggesting that the hydrolysis of dinucleoside polyphosphates may be a more important physiological function of NPPs.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is noteworthy that NPPs prefer alkaline pHs for activity. In our hands, recombinant human NPP1 and NPP3 had only low ATPase activities (compared with those of NTPDases) [17], suggesting that the hydrolysis of dinucleoside polyphosphates may be a more important physiological function of NPPs.…”
Section: Introductionmentioning
confidence: 69%
“…The ATP analogue 6-N, Ndiethyl-D-β,γ-dibromomethylene ATP (ARL 67156) is another commercially available ecto-ATPase inhibitor that does not affect significantly purinoceptors. Recent reports demonstrated that ARL 67156 is a weak competitive inhibitor of NTPDase1, NTPDase3 and NPP1, with K i for the human enzymes of 11± 3, 18± 4 and 12± 3 µM, respectively [17,68]. Another ATP analogue, 8-thiobutyladenosine 5′-triphosphate (8-BuS-ATP), and 1-naphthol-3,6-disulfonic acid (BG0136), appear of interest, but so far they have only been characterised on a NTPDaseactive fraction from bovine spleen membranes [69,70].…”
Section: Inhibitors Of Ectonucleotidasesmentioning
confidence: 99%
“…E-mail: lovatt@upenn.edu or nedergaard@ urmc.rochester.edu. only partially inhibits ATP dephosphorylation (17)(18)(19), suggesting that several NTPdases-including CD39, NTPDase-2 and -3, and alkaline phosphatase-are functional in brain tissue.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to ␣,␤-methylene ADP, it did not significantly recover arteriolar constrictions to ATP: 1 Ϯ 1% constriction to ATP and 7.1 Ϯ 3% constriction to ATP following preincubation in ARL-67156 (P ϭ 0.09, Mann-Whitney test, n ϭ 8 each). In a recent study of the effect of ARL-67156 on recombinant mouse and human CD39 family members, Levesque et al (21) reported that mouse CD39 is only 50% inhibited by ARL-67156 when the ratio of antagonist to ATP is 10:1. This may account for the relatively small recovery of constrictions to ATP after ARL-67156 treatment.…”
Section: Resultsmentioning
confidence: 99%